The origins of the constitutional precedent in Peru - García Belaunde, Domingo (2020)
The purpose of the article is to provide a historical approach on how and when the precedent was introduced into Peruvian positive law. To this end, the draft law discussed and prepared by the 1981 Commission will be analyzed, as well as the reforms which it was submitted due to the constitutional changes, until the current Constitutional Procedural Code. This based on the experience of the author, who was part of this process and the broad dialogue built around the precedent.